Sexual functioning in people with stable chronic diseases - Pais-Ribeiro, José Luís (2016)
Backgound - In developed countries people are living longer and the incidence of chronic disease (CD) is increasing. CD and its treatments can have a negative impact on sexual functioning and sexual satisfaction. Objective - To explore and to compare sexual function and sexual satisfaction in people with stable chronic diseases.